2001
DOI: 10.1101/gr.155301
|View full text |Cite
|
Sign up to set email alerts
|

Microchip Module for Blood Sample Preparation and Nucleic Acid Amplification Reactions

Abstract: A computer numerical control-machined plexiglas-based microchip module was designed and constructed for the integration of blood sample preparation and nucleic acid amplification reactions. The microchip module is comprised of a custom-made heater-cooler for thermal cycling, a series of 254 µm × 254 µm microchannels for transporting human whole blood and reagents in and out of an 8-9 µL dual-purpose (cell isolation and PCR) glass-silicon microchip. White blood cells were first isolated from a small volume of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 16 publications
1
73
0
1
Order By: Relevance
“…Considering that M13/pUC is a well established cloning vector and the assay was carried out in a buffer environment, the prospective inhibition from a matrix of 'real' sample (blood sample and/or with whole target cells) was not present. The PC plastic serpentine channel PCR micro reactor discussed in this study held a maximum volume of 40 ml and demonstrated a high sensitivity of amplifying 10 E. coli cells (50 fg DNA) from 2% blood sample, as compared to on-chip (glass-silicon) amplification of ng amounts of WBC DNA obtained by filtration from a sample containing 3 ml of blood (30) and/or PCR from a 1% blood 31 sample in fused-silica capillaries. Although 40 ml is not commonly considered a very small volume, this plastic PCR micro reactor was designed and fabricated with the intent of total on-chip integration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that M13/pUC is a well established cloning vector and the assay was carried out in a buffer environment, the prospective inhibition from a matrix of 'real' sample (blood sample and/or with whole target cells) was not present. The PC plastic serpentine channel PCR micro reactor discussed in this study held a maximum volume of 40 ml and demonstrated a high sensitivity of amplifying 10 E. coli cells (50 fg DNA) from 2% blood sample, as compared to on-chip (glass-silicon) amplification of ng amounts of WBC DNA obtained by filtration from a sample containing 3 ml of blood (30) and/or PCR from a 1% blood 31 sample in fused-silica capillaries. Although 40 ml is not commonly considered a very small volume, this plastic PCR micro reactor was designed and fabricated with the intent of total on-chip integration.…”
Section: Discussionmentioning
confidence: 99%
“…An automated and integrated system for high-throughput DNA genotyping directly from blood was reported by Zhang et al 31 Using a hot air thermocycler, samples containing whole blood were directly amplified in a fused-silica capillary and only one concentration (1%) of blood sample PCR was demonstrated, providing ng amounts of DNA as the starting genomic material. In another microchip module for blood sample preparation and amplification, Wilding's group demonstrated direct capture of WBC cells in a glass-silicon microchip with a series of micro filters, from 3 ml of whole human blood, and subsequent amplification of human coagulation factor V from WBC DNAs in the same microchip, 30 in which > 10 ng WBC genomic DNA was used as initial template. For on-chip PCR from a blood sample in our PC plastic PCR micro reactor, the initial denature time was prolonged to 15 min, using the Hot Start Taq DNA polymerase (QIAgen Valencia, CA), and also supplemented with Q buffer (QIAgen) which is designed to accommodate the blood components which could inhibit PCR.…”
Section: Discussionmentioning
confidence: 99%
“…A PCR-t összekapcsolva más folyamatokkal, egy komplexebb rendszert is ki lehet alakítani [17]. A megoldás egy olyan eszköz, amely képes a sejtek elkülöníté-sére és a PCR-amplifi kációs feladat megvalósítására.…”
Section: Mikrofl Uidikai Eszközökben Megvalósított Nukleinsav-alapú Munclassified
“…The device was fabricated by standard photolithographic techniques and was molded in PDMS, from an SU8 master. Wilding's group used weir-like structure to create a 3.5 µm space between the silicon bottom and a glass top of a device to separate WBCs from whole blood, they could then use the cell's DNA for amplification [82][83][84].…”
Section: Separation Of Cells By Sizementioning
confidence: 99%